Ravi Jagannathan (Journal of Finance, 2024)
Ravi's research made methodological contributions to the field of asset pricing that helped in the use of asset markets data to guide the development of superior models, which has improved our understanding of how asset prices are linked to the economy, and how investors behave.His joint work with Lars Hansen (Journal of Political Economy, 1991 and The Journal of Finance, 1997) shows that the mean variance frontier of returns, familiar to finance academics as well as professionals, contains interesting information about how investors trade current payoffs for risky future payoffs even when risk is not characterized just by the variances of the payoffs.They showed that observed returns on securities provide additional information about investors' preferences when there are no arbitrage opportunities in financial markets.The market risk premium (MRP), which is the expected return on the market above the risk-free return, plays an important role in corporate finance as a component of the cost of capital.It is well-recognized that historical average MRP is a very noisy measure, and theoretical models of how investors behave are necessary to provide confidence in estimates of what the MRP will be going forward.The papers developed two measures summarizing the information in asset returns about investors' preferences, Hansen-Jagannathan Bound and Hansen-Jagannathan Distance, both of which provide guidance for developing theoretical models of MRP.